Phosphoinositide 3-kinase and the mammalian target of rapamycin pathways control T cell migration. - Finlay, David (My University, 2010)
The established role for phosphatidylinositol (3,4,5) triphosphate (PI(3,4,5)P3) signaling pathways is to regulate cell metabolism. More recently it has emerged that PI(3,4,5)P3 signaling via mammalian target of rapamycin and Foxo transcription factors also controls lymphocyte trafficking by determining the repertoire of adhesion and chemokine receptors expressed by T lymphocytes. In quiescent T cells, nonphosphorylated active Foxos maintain expression of KLF2, a transcription factor that regulates expression of the chemokine receptors CCR7 and sphingosine 1 phosphate receptor, and the adhesion receptor CD62L that together control T-cell transmigration into secondary lymphoid tissues. PI(3,4,5)P3 mediates activation of protein kinase B, which phosphorylates and inactivates Foxos, thereby terminating expression of KLF2 and its target genes. The correct localization of lymphocytes is essential for effective immune responses, and the ability of phosphoinositide 3-kinase and mammalian target of rapamycin to regulate expression of chemokine receptors and adhesion molecules puts these signaling molecules at the core of the molecular mechanisms that control lymphocyte trafficking.
PUBLISHED
Keywords: Immunology; T cells; Immunology, Inflammation & Infection